The Effect of Mixing Time and Mixing Sequence during Processing on the Physicochemical and Sensory Properties of Keropok Lekor - Murad, Najwa Shamila; Ismail, Mohamad Afifi; Nor-Khaizura, Mahmud Ab Rashid; Ismail-Fitry, Mohammad Rashedi (Journal of Science and Technology, 2017)
The common practice of mixing in keropok lekor processing is carried out continuously to produce a homogenize batter with no specific time and sequence established yet. The goal of the work was to study the effect of different mixing time and sequence (intermittent and continuous) against the physicochemical and sensory properties of keropok lekor.  The  keropok lekor batter was mixed for 6, 12 or 18 min non-stop for the continuous mixing, while  the  intermittent mixing was carried out for 6  min  (2  min  mix and 2  min break),  12  min  (4  min  mix and 2  min break),  and  18  min  (6  min  mix and 2  min break).  The  intermittent  mixing  for  6  min  was the best method among all the treatments, where the results  for  the  moisture  content  (56.60±2.20),  protein  content  (10.23±1.21),  water  holding  capacity  (83.33±11.02),  linear  expansion  (5.86±2.32),  cooking  yield  (107.15±0.60),  lightness, redness and yellowness (colour), hardness, cohesiveness, springiness and chewiness (texture profile analysis) and  sensory  evaluation  scores were equivalent (p>0.05) or better (p